ANALISIS KEBIJAKAN PUBLIK DAN HUKUM PIDANA DALAM PERSPEKTIF PERLINDUNGAN KOSUMEN PENGGUNA PINJAMAN ONLINE (PINJOL) - Saepudin, Eli Apud; Agustiawan, M. Nassir; Asnawi, Asnawi (LPPM Universitas Bina Bangsa, 2024)
Nowadays, people are lulled by the proliferation of online loans which are very easy to get using an Android smartphone, quota, e-KTP, selfie photo and smartphone number. In less than five minutes, the liquid money is received by consumers into their personal accounts, first loan, second loan and so on. third loan and so on and in the end, all the online loan applications available on Playstore can be downloaded, there can be up to ten or even more loans downloaded on smartphones. Unfortunately, because there are so many loans whose funds are credited to personal accounts at the same time as the payment is due, consumers are terrorized day and night, even holidays are billed as well as confusion about paying because the money has run out to meet consumer needs, based on government policy through the Financial Services Authority Non-bank Payment Service Providers (PJP), Aggregators and Cooperatives collaborate or facilitate illegal online loans, and are required to comply with the principle of recognizing service users ( Know Your Customer) in accordance with applicable laws and regulations, this means that illegal online loans may not be paid, while legal loans must be paid. If consumers who use legal loans do not pay, they will be included in the BI Checking list and blacklisted by the OJK, meaning consumers cannot borrow either from banks or other loans, consumers can be punished if they fail to pay the loan. However, in Article 19 paragraph (2) of Law no. 39 of 1999 concerning Human Rights, consumers will not be punished, but if they have a bad credit history, their name will be on the OJK's bad credit blacklist